Emulation of Spiking Response and Spiking Frequency Property in VCSEL-Based Photonic Neuron - Shuiying Xiang; Aijun Wen; Wei Pan (IEEE Photonics Journal)
The dynamical response properties of photonic neuron based on vertical-cavity surface emitting lasers (VCSELs) subject to orthogonal polarized optical pulse injection stimuli have been numerically investigated. Based on the well-known spin flip model, we first reproduce some experimental findings of neuron-like dynamics in VCSELs, such as phasic spiking with a single abrupt pulse, and tonic spiking with multiple periodic pulses. Besides, we further go beyond in three directions and obtain several novel results. The operating parameter ranges corresponding to different neuron-like dynamics are identified by extensive bifurcation analysis. In addition, the effect of the time-varying pump current on the neuron-like dynamics for VCSELs under given optical injecting pulse strength is also discussed. For a given pump current, the spiking frequency dependence on the stimuli strength is further revealed in VCSELs with time-varying optical pulse injection. Such controllable neuron-like response dynamics and spiking frequency dependence in VCSELs are interesting and valuable for ultrafast photonic neuromorphic systems and neuron-inspired photonic information processing.